2020
DOI: 10.1101/2020.10.30.361618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of transparency indicators across the biomedical literature: how open is open?

Abstract: Recent concerns about the reproducibility of science have led to several calls for more open and transparent research practices and for the monitoring of potential improvements over time. However, with tens of thousands of new biomedical articles published per week, manually mapping and monitoring changes in transparency is unrealistic. We present an open-source, automated approach to identify five indicators of transparency (data sharing, code sharing, conflicts of interest disclosures, funding disclosures an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Furthermore, we charted differences in transparency practices between 59 distinct clinical medicine disciplines over time. The sensitivity and specificity of the rtransparent tool (17) were used to generate 95% confidence intervals (CIs) for the estimates of the transparency practices. We used visual presentation and Pearson's product-moment correlation to analyze the yearly trend in transparency practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we charted differences in transparency practices between 59 distinct clinical medicine disciplines over time. The sensitivity and specificity of the rtransparent tool (17) were used to generate 95% confidence intervals (CIs) for the estimates of the transparency practices. We used visual presentation and Pearson's product-moment correlation to analyze the yearly trend in transparency practices.…”
Section: Discussionmentioning
confidence: 99%
“…We used the rtransparent package (17), a validated and automated programmatic tool (13), to identify five transparent practices from the full texts we were able to download from EPMC:…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…The searches and data export from the EPMC were conducted with the europepmc package [16]. Indicators of transparency practices from the available full texts were extracted with the rtransparent package [17]. Trends over time in transparency practices were reported using descriptive tabulations and visualizations using the ggplot2 package [18].…”
Section: Discussionmentioning
confidence: 99%
“…18 Our previous analysis of journals' endorsements, however, showed that only 13% of journals across disciplines recommended the use of reporting guidelines, and only 2% required it. 15 Data sharing practices across sciences have not been systematically explored, but recent estimates indicated that data sharing was mentioned in 15% of biomedical, 19 and in only 2% of psychological articles. 20 A 2020 systematic review indicated that most researchers have positive attitudes toward data sharing.…”
Section: Discussionmentioning
confidence: 99%